Generation of pharmacophores and classification of drugs using protein-ligand complexes (2012)
Pharmacophore identification is a veryimportant step in de novo design, leadoptimization, chemogenomics, and virtualscreening of drugs. Unfortunately,the high cost of comercial software forpharmacophore detection is a commonlimiting factor for researchers with limitedfunding. This paper presents a set offreely available perl routines that weredesigned to help in the process of 3Dpharmacophore identification and QSARstudies. These routines also allowed theclassification of ligands based on theirtridimensional similarity and bindingmechanism. The family of phosphodiesterasesand their inhibitors were used astest model.